Carbon dioxide and plastic waste utilization coupling electrolysis method for membrane electrode stack

By using nickel unit dot/silver nanoparticle composite material and iron hydroxide/manganese carbonate self-supporting electrodes to form a dual-electrode system, the problems of low catalytic activity, low current density and poor stability in the prior art are solved, and efficient carbon dioxide is achieved Reduction and PET hydrolysate oxidation, the product Faraday efficiency and good stability.

CN119433605AActive Publication Date: 2025-02-14DALIAN UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411618508.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

In the prior art, the catalytic activity is low, the current density is low, the stability is poor, and it is difficult to effectively utilize carbon dioxide and plastic waste.

Method used

Nickel unit point/silver nanoparticle composite material is used as the cathode electrode and iron hydroxide/manganese carbonate self-supporting electrode as the anode. Nickel unit point/silver nanoparticle electrode is prepared by calcining method, and self-supporting electrode with iron hydroxide/manganese carbonate self-supporting electrode A dual electrode system is formed to achieve coupled electrolysis of carbon dioxide reduction and PET hydrolysate oxidation.

Benefits of technology

The synthesis of carbon monoxide and formic acid under industrial-grade current density was achieved, the Faraday efficiency of the cathode and anode product remained above 95%, and the stability of the catalyst was significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433605A_ABST
    Figure CN119433605A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon dioxide and plastic waste utilization coupling electrolysis method for a membrane electrode stack, and belongs to the technical field of electro-catalytic materials and devices. A nickel unit dot / silver nanoparticle composite material is synthesized by using a calcination method, and the catalyst is loaded on a gas diffusion electrode and is respectively used for carbon dioxide reduction and plastic hydrolysate oxidation together with a ferric hydroxide / manganese carbonate self-supporting electrode, so that a coupling electrolysis system for carbon dioxide and plastic waste utilization is constructed; and the preparation of industrial grade current density of carbon monoxide and formic acid is realized. In a 2 * 2 cm < 2 > membrane electrode device, under the cell pressure of 2.4 V, the coupling system can realize the industrial grade current density of 800 mA / cm < 2 >, and the Faraday efficiencies of carbon monoxide and formic acid of a cathode and an anode are both kept at 95% or above. The area of the electrode is further enlarged to 10 * 10 cm < 2 >, and the electrode is assembled into a membrane electrode stack capable of being assembled with five electrodes, so that the preparation of carbon monoxide and formic acid ampere-level current is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic materials and devices, and relates to a coupled electrolysis method for utilizing carbon dioxide and plastic waste for membrane electrode stacks, and specifically relates to oxidation of anode plastic hydrolysate to produce formic acid, reduction of cathode carbon dioxide to produce carbon monoxide, and assembly of membrane electrodes. Background Art

[0002] As an important industrial material, plastic has become an essential part of contemporary life, with an annual global production of more than 380 million tons. As a common polyester plastic, polyethylene terephthalate (PET) is widely used in food / beverage packaging, medical supplies, electronic products and polyester fibers, but its natural decomposition rate is relatively slow, leading to serious environmental pollution. Therefore, effective strategies are needed to degrade and recycle waste plastics. At present, the technologies for recycling PET plastics include mechanical, biological and chemical methods. Among them, the chemical route shows greater potential in upgrading and recycling PET plastic waste, in which PET plastic can be effectively hydrolyzed into terephthalic acid and ethylene glycol monomers under alkaline conditions, and ethylene glycol can be further synthesized into the desired chemicals through chemical oxidation. In addition, as one of the main waste gases of the greenhouse effect, excessive emission of carbon dioxide will destroy the ecological balance and cause a series of environmental problems. As an abundant carbon-one small molecule, carbon dioxide can be further converted into higher-value chemicals by electrochemical means. Therefore, the all-electrolysis system that couples carbon dioxide reduction and PET hydrolyzate oxidation can realize the waste utilization of plastics, greenhouse gases and flue gases.

[0003] For the construction of a co-electrolysis system for the utilization of carbon dioxide and plastic waste, efficient anode and cathode electrocatalysts are essential. Single-site catalysts and single-atom catalysts are widely used in the field of catalysis due to their efficient atomic utilization and excellent catalytic performance. However, single-metal site catalysts are prone to agglomeration during long-term catalytic reactions, resulting in decreased stability, which is the main reason restricting their development. In addition, for the carbon dioxide reduction reaction, the single-metal site catalyst adsorbs carbon dioxide molecules too strongly, making it difficult to desorb the product, and further regulation of the catalyst is also needed to balance the adsorption and desorption problems. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention couples carbon dioxide reduction with PET hydrolyzate oxidation, thereby realizing waste utilization of carbon dioxide and plastics. For the cathode carbon dioxide reduction reaction, a composite material of nickel unit site / silver nanoparticles is synthesized by a calcination method, and the charge structure is adjusted by adjusting the amount of silver added, and the generation of carbon monoxide is promoted by the synergistic effect of nickel and silver. The anode uses a water oxidation electrode (iron hydroxide / manganese carbonate self-supporting electrode) for the PET hydrolyzate oxidation reaction, and promotes the generation of formic acid by the synergistic effect of iron and manganese. A gas diffusion electrode loaded with nickel unit site / silver nanoparticles and an iron hydroxide / manganese carbonate self-supporting electrode are combined into a full-cell electrolysis system to realize the synthesis of carbon monoxide and formic acid at an industrial-grade current density.

[0005] The purpose of the present invention is to provide a coupled electrolysis method for utilizing carbon dioxide and plastic waste for a membrane electrode stack, mainly to solve the problems of low catalytic activity, low current density, poor stability, etc. in the prior art.

[0006] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is as follows: a method for coupled electrolysis of carbon dioxide and plastic waste for membrane electrode stack, using nickel unit point / silver nanoparticle electrode as cathode and iron hydroxide / manganese carbonate self-supporting electrode as anode to assemble membrane electrode assembly, and electrolysis is performed; carbon dioxide with a gas velocity of 20-40 ml / min is introduced into the cathode flow channel, polyethylene terephthalate hydrolyzate with a flow velocity of 10-30 ml / min is introduced into the anode flow channel, and an anion exchange membrane is arranged between the cathode and the anode;

[0007] The method for preparing the nickel unit site / silver nanoparticle electrode comprises the following steps:

[0008] S1. Place nickel nitrate, silver nitrate and dicyandiamide in a test tube, add anhydrous ethanol dropwise, and disperse uniformly by ultrasonication to obtain a mixed solution; the ratio of nickel nitrate: silver nitrate: dicyandiamide: anhydrous ethanol is (0.5-1.5) g: (0.2-0.6) g: (2-3) g: (1-3) mL;

[0009] S2, pour the mixed solution into a quartz boat, place it in a tube furnace, and calcine it in an argon atmosphere; the argon flow rate is 10-30 ml / min; the tube furnace heating rate is 2-5 °C / min, the maximum temperature is 900-1100 °C, and the holding time is 2-4 hours;

[0010] S3. After calcination, take out the powder and place it in a dilute sulfuric acid solution for pickling;

[0011] S4, after acid washing, centrifugation was performed with deionized water and anhydrous ethanol respectively;

[0012] S5, after centrifugation, placing the obtained material in a vacuum drying oven and drying overnight to obtain a nickel unit site / silver nanoparticle composite material;

[0013] S6. Weigh the nickel unit site / silver nanoparticle composite material, ultrasonically disperse it in a mixture of Nafion and anhydrous ethanol, spray the suspension onto a gas diffusion electrode, and vacuum dry it to obtain a nickel unit site / silver nanoparticle electrode.

[0014] Furthermore, the concentration of the dilute sulfuric acid is 0.1-1 mol / l, the pickling time is 5-10 hours, and the pickling temperature is 50-100°C.

[0015] Furthermore, the particles in the nickel unit site / silver nanoparticle electrode exist in the morphology of hollow nanotubes.

[0016] Furthermore, the preparation method of the iron hydroxide / manganese carbonate self-supporting electrode (reference preparation method in CN112342563A):

[0017] S1, ultrasonically washing the nickel foam substrate with dilute hydrochloric acid, anhydrous ethanol and ultrapure water respectively to obtain a nickel foam substrate after ultrasonic washing;

[0018] S2. A mixed solution of manganese chloride and urea is added to a hydrothermal reactor lined with polytetrafluoroethylene, and the foamed nickel substrate after ultrasonic cleaning is immersed in the above solution, and a hydrothermal reaction is carried out at 120° C. for 8-15 hours to obtain a foamed nickel electrode loaded with manganese carbonate; the concentration of urea in the mixed solution is 0.1-0.2 mol / L, and the concentration of manganese chloride solution is 0.01-0.05 mol / L;

[0019] S3, placing the manganese carbonate-loaded nickel foam electrode in a ferric nitrate solution, using a three-electrode system for electrodeposition to obtain an iron hydroxide / manganese carbonate-nickel foam self-supporting electrode, with a deposition potential of -0.8V-1.5V and a deposition time of 100-600s;

[0020] The concentration of the ferric nitrate solution is 0.005-0.02 mol / L;

[0021] S4. Wash with ultrapure water to remove residual ions on the surface, and dry naturally to obtain an iron hydroxide / manganese carbonate-nickel foam self-supporting electrode.

[0022] Furthermore, a membrane electrode stack is assembled by using a plurality of groups of the above-mentioned membrane electrode assemblies.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention synthesizes a nickel unit site / silver nanoparticle composite material by calcination method, which is used for the study of electrocatalytic carbon dioxide reduction to carbon monoxide. A gas diffusion electrode loaded with nickel unit site / silver nanoparticles and an iron hydroxide / manganese carbonate self-supporting electrode form a double electrode for the construction of a carbon dioxide reduction coupled PET hydrolyzate oxidation full electrolysis cell. In a membrane electrode device, at a cell voltage of 2.4 V, the coupled system can achieve 800 mA / cm 2 At industrial-grade current density, the Faraday efficiencies of carbon monoxide and formic acid at the cathode and anode are both maintained above 95%. This excellent catalytic performance and stability are mainly attributed to the synergistic effect of nickel-silver at the cathode and iron-manganese at the anode.

[0025] (1) The nickel single-site / silver nanoparticle catalyst prepared in the present invention has better catalytic activity and stability than the nickel single-site catalyst.

[0026] (2) The strategy of replacing water oxidation with oxidation of anodic PET hydrolysate in the present invention reduces the cell pressure of the system and realizes the co-production of cathodic and anodic chemicals.

[0027] (3) The present invention uses the carbon dioxide reduction-coupled PET hydrolyzate oxidation system for the assembly of a large-area membrane electrode stack, achieving the synthesis of carbon monoxide and formic acid at an industrial-grade current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The linear voltammetric curve, impedance diagram, electrochemically active surface area diagram, and Tafel slope diagram of the bismuth / bismuth oxide heterojunction electrode.

[0029] Figure 2 This is a stability test diagram when the cathode is a nickel unit site or a nickel unit site / silver nanoparticle 2 gas diffusion electrode and the anode is an iron hydroxide / manganese carbonate self-supporting electrode.

[0030] Figure 3 Cyclic voltammograms of the cathode catalysts at different scan rates at non-Faraday potentials of -0.1 to 0 V.

[0031] Figure 4 Impedance fitting diagram of each cathode catalyst.

[0032] Figure 5 X-ray diffraction spectra of various cathode catalysts.

[0033] Figure 6 Spherical aberration electron microscopy images of nickel unit site and nickel unit site / silver nanoparticle 2.

[0034] Figure 7 2 are scanning electron micrographs of nickel unit sites and nickel unit sites / silver nanoparticles 2.

[0035] Figure 8 X-ray photoelectron spectra of various catalyst elements.

[0036] Fig. 9 The specific surface area of ​​each catalyst was tested.

[0037] Fig.10 Raman spectroscopy characterization of each catalyst.

[0038] Fig.11 This is a test of the hydroxide adsorption of each catalyst.

[0039] Fig.12 Carbon dioxide adsorption and desorption tests of various catalysts.

[0040] Fig.13 Carbon monoxide adsorption and desorption tests of various catalysts.

[0041] Fig.14 10*10 cm 2 Gas diffusion electrode assembly and test diagram.

[0042] Fig.15 5 pieces of 10*10 cm 2 Membrane electrode stack composed of gas diffusion electrodes and test diagram. DETAILED DESCRIPTION

[0043] The present invention is further described below in conjunction with the accompanying drawings and examples. The embodiments of the present invention include but are not limited to the following examples.

[0044] A coupled electrolysis method for utilizing carbon dioxide and plastic waste for a membrane electrode stack comprises the following steps:

[0045] S1. Place nickel nitrate, silver nitrate and dicyandiamide in a test tube, add anhydrous ethanol dropwise, and disperse evenly by ultrasonication; the amount of nickel nitrate added is 0-1 g, the amount of silver nitrate added is 0-0.6 g, the amount of dicyandiamide added is 2-3 g, and the amount of anhydrous ethanol added is 1-3 ml;

[0046] S2, pouring the mixed solution obtained in (S1) into a quartz boat, placing it in a tube furnace, and calcining it in an argon atmosphere; the argon flow rate is 10-30 ml / min; the heating rate of the tube furnace is 2-5 °C / min, the maximum temperature is 900-1100 °C, and the holding time is 2-4 hours;

[0047] S3. After calcination, the powder is taken out and placed in a dilute sulfuric acid solution for pickling; the dilute sulfuric acid concentration is 0.1-1 mol / l, the pickling time is 5-10 hours, and the pickling temperature is 50-100 °C;

[0048] S4, after pickling, centrifugation washing with deionized water and anhydrous ethanol respectively;

[0049] S5, after centrifugation, placing the obtained material in a vacuum drying oven and drying overnight to obtain a nickel unit site / silver nanoparticle composite material;

[0050] S6. Weigh the nickel unit site / silver nanoparticle composite material, ultrasonically disperse it in a mixture of Nafion and anhydrous ethanol, spray the suspension onto a gas diffusion electrode, and vacuum dry it to obtain a nickel unit site / silver nanoparticle gas diffusion electrode.

[0051] A nickel unit site / silver nanoparticle gas diffusion electrode and an iron hydroxide / manganese carbonate self-supporting electrode were used as the anode and cathode to form a dual-electrode system. Carbon dioxide was introduced into the cathode at a rate of 20-40 ml / min, and PET hydrolyzate was introduced into the anode at a flow rate of 10-30 ml / min. The anode and cathode were separated by an anion exchange membrane and tested on an electrochemical workstation and a DC power supply.

[0052] The specific embodiments are as follows:

[0053] Examples 1-4

[0054] The specific steps for preparing the nickel unit site / silver nanoparticle composite material are as follows: 1 g nickel nitrate, 0-0.4 g silver nitrate and 2.9 g dicyandiamide are placed in a test tube, 2 ml anhydrous ethanol is added dropwise, and ultrasonic dispersion is uniform; then the mixed solution is poured into a quartz boat and placed in a tubular furnace for calcination under an argon atmosphere, and the argon flow rate is 20 ml / min; the heating rate of the tubular furnace is 3 °C / min, the maximum temperature is 100 °C, and the holding time is 3.5 hours; after the calcination is completed, the powder is taken out and placed in a dilute sulfuric acid solution for pickling; the dilute sulfuric acid concentration is 0.5 mol / l, the pickling time is 8 hours, and the pickling temperature is 80 °C; after pickling, it is centrifugally washed three times with deionized water and anhydrous ethanol respectively; finally, it is placed in a vacuum drying oven and dried overnight at 60 °C. The amount of silver nitrate added was 0, 0.2, 0.3, and 0.4 g, and the prepared catalyst materials were nickel unit site (Example 1), nickel unit site / silver nanoparticle 1 (Example 2), nickel unit site / silver nanoparticle 2 (Example 3), and nickel unit site / silver nanoparticle 3 (Example 4). The catalysts were characterized by a series of instruments such as X-ray diffraction, X-ray photoelectron spectroscopy, and scanning electron microscopy.

[0055] Weigh 25 mg of the above catalyst and ultrasonically disperse it in 2.25 ml of anhydrous ethanol and 0.25 ml of 5% Nafion solution. Take a quantitative amount of the catalyst dispersion and spray it on the gas diffusion electrode with a loading of 0.5 mg / cm 2 .

[0056] Preparation method of ferric hydroxide / manganese carbonate self-supporting electrode (publication number: CN112342563A): The nickel foam substrate is ultrasonically washed with dilute hydrochloric acid, anhydrous ethanol, and ultrapure water for 20 minutes to remove the oxides and organic impurities remaining on the nickel foam. Then, 40 ml of a mixed aqueous solution of manganese chloride and urea is added to a stainless steel hydrothermal reactor, wherein the concentration of the manganese chloride solution is 0.025 mol / L and the concentration of the urea solution is 0.125 mol / L. The nickel foam is immersed in the solution for a hydrothermal reaction at 120°C for 11 hours; then, in a 0.01 mol / L ferric nitrate solution, a three-electrode system is used for electrodeposition, the deposition potential is -1V (vsAg / AgCl electrode), and the deposition time is 300s. Finally, a self-supporting electrode of ferric hydroxide / manganese carbonate-nickel foam is obtained.

[0057] The prepared nickel unit point / silver nanoparticle electrode was used as the cathode and the iron hydroxide / manganese carbonate self-supporting electrode was used as the anode to form a membrane electrode assembly. The cathode and cathode areas were both 2*2 cm 2 Carbon dioxide was introduced into the cathode at a flow rate of 30 ml / min, and PET hydrolyzate was introduced into the anode at a flow rate of 20 ml / min. The cathode and cathode were separated by an anion exchange membrane, and the test was carried out on an electrochemical workstation and a DC power supply.

[0058] like Figure 1 As shown in Figures ab, the membrane electrode assembly was subjected to a linear voltammetric test in the voltage range of 0 to 3 V. It can be seen that the nickel unit site / silver nanoparticle 2 gas diffusion electrode has the best catalytic performance when used as the cathode; Figure 1 c and 1e are the constant potential electrolysis diagrams of nickel unit site and nickel unit site / silver nanoparticle 2 in the range of 1.9-2.4 V, respectively, and the anode and cathode products are quantitatively analyzed and calculated, such as Figure 1 Figures 1d and 1f are the Faraday efficiency diagrams of the cathode products when the cathode is nickel unit site and nickel unit site / silver nanoparticle 2, respectively. The Faraday efficiency of the product carbon monoxide of nickel unit site / silver nanoparticle 2 is above 95%, reaching a maximum of 98% at 2.2 V. At 2.4 V, the carbon monoxide current density reached 800 mA / cm 2 The above shows excellent selectivity and industrial-grade current density. However, the highest Faraday efficiency of carbon monoxide for nickel single-site catalysts is only 83% in the voltage range of 1.9~2.4 V. The Faraday efficiency of formic acid produced by the anode iron hydroxide / manganese carbonate self-supporting electrode remains above 95% in the voltage range of 1.9~2.4 V. This excellent catalytic activity is mainly attributed to the synergistic effect of nickel-silver and iron-manganese.

[0059] When the cathode is a nickel unit site / silver nanoparticle 2 gas diffusion electrode, the current density can be stable for more than 100 hours at a voltage of 2.2 V, and the anode and cathode carbon monoxide and formic acid Faraday efficiency does not decay; at the same voltage, when the cathode is a nickel unit site gas diffusion electrode, the cathode carbon monoxide Faraday efficiency has decayed significantly after more than 20 hours. This proves that the introduction of silver nanoparticles can improve the stability of the catalyst.

[0060] Figure 3 The cyclic voltammetry curves of each cathode catalyst at different scan rates at non-Faraday potentials of -0.1 to 0 V are used to calculate the double-layer capacitance value, such as Figure 3 e is the double layer capacitance of each catalyst. The nickel unit site / silver nanoparticle 2 has the highest double layer capacitance of 9.2 mFcm -2 The higher double layer capacitance value indicates a higher electrochemical active area.

[0061] Figure 4 The impedance fitting diagram of each catalyst at the cathode shows that nickel unit point / silver nanoparticle 2 has the smallest semicircle diameter, indicating that it has the fastest charge transfer rate.

[0062] Figure 5 It is the X-ray diffraction spectrum of each cathode catalyst. The nickel unit point is mainly the diffraction peak of metallic nickel, and the nickel unit point / silver nanoparticle is mainly the diffraction peak of metallic silver.

[0063] Figure 6 The spherical aberration electron microscopy images of the nickel unit site and the nickel unit site / silver nanoparticle 2 show uniformly distributed single metal sites. Combined with the fact that no diffraction peak of nickel was observed in the X-ray diffraction spectrum of the nickel unit site / silver nanoparticle, it is proved that the metallic nickel is distributed in a unit site.

[0064] Figure 7 3 and 4 are scanning electron microscope images of the nickel unit site and the nickel unit site / silver nanoparticle 2. It is observed that the nickel unit site has a nanotube morphology, and the nickel unit site / silver nanoparticle 2 has a nanotube and nanoparticle morphology.

[0065] Figure 8 is the X-ray photoelectron spectrum of each catalyst element. Figure 8 In the spectrum where b is nitrogen, peaks of pyridinic nitrogen, metal-nitrogen, pyrrolic nitrogen, and graphitic nitrogen were observed, which also confirmed that the existence state of the nickel unit site is nickel-nitrogen-carbon coordination; Figure 8 From the spectrum where c is nickel, it can be observed that after silver doping, the characteristic peak of nickel shifts to the place with smaller binding energy, indicating that the nickel in the nickel unit site / silver nanoparticle 2 is in a charge-enriched state, confirming the synergistic effect of nickel and silver.

[0066] Fig. 9For the specific surface area test of each catalyst, nickel unit site / silver nanoparticle 2 has the largest specific surface area of ​​169.2.

[0067] Fig.10 For the Raman spectroscopy characterization of each catalyst, the adsorption bands (I D ) and graphite ribbon (I G ) ratio, the nickel unit site / silver nanoparticle 2 has the largest I D / I G The value indicates that it has larger carbon defects inside. Carbon defects are conducive to more stable anchoring of single atom sites.

[0068] Fig.11 To test the hydroxyl adsorption of each catalyst, the adsorption capacity of carbon dioxide reduction intermediates was evaluated by simulating hydroxyl adsorption. As shown in the figure, nickel unit site / silver nanoparticle 2 has a more negative hydroxyl adsorption potential, which is inferred to have a better adsorption capacity for carbon dioxide reduction intermediates.

[0069] Fig.12 In the carbon dioxide adsorption and desorption tests of each catalyst, the desorption temperature of nickel single site / silver nanoparticle 2 is the highest, indicating that it has the strongest carbon dioxide adsorption capacity, and at the same time proves that the combination of nickel and silver improves the catalyst's adsorption capacity for carbon dioxide.

[0070] Fig.13 The carbon monoxide adsorption and desorption tests of each catalyst showed that the desorption temperature and peak intensity of the nickel unit point were the strongest, indicating that its desorption ability for carbon monoxide was the weakest. Combined with the previous stability test of the nickel unit point ( Figure 2 In figure a), it is speculated that the decrease in the activity of the nickel single-site catalyst may be due to carbon monoxide poisoning and deactivation. Silver nanoparticles and nickel single sites are beneficial to enhance the desorption of carbon monoxide, improve the stability of the catalyst and prevent carbon monoxide poisoning.

[0071] Example 5

[0072] Enlarging the gas diffusion electrode to 10*10 cm 2 The iron hydroxide / manganese carbonate self-supporting electrode was also enlarged to 10*10cm 2 For membrane electrode devices. Fig.14 10*10 cm 2 Gas diffusion electrode assembly and test diagram, to which different voltages are applied to compare the current of carbon dioxide reduction coupled with water oxidation and coupled with plastic hydrolysate oxidation, Fig.14 In Figure c, it can be seen that the carbon dioxide reduction coupled with plastic hydrolyzate oxidation has a higher current. At a voltage of 3.8 V, the carbon dioxide reduction coupled with plastic hydrolyzate oxidation membrane electrode assembly current reached 51.9 A, and the Faraday efficiency of carbon monoxide and formic acid remained above 80%.

[0073] Example 6

[0074] Put five pieces of 10*10 cm 2 The gas diffusion electrode and the iron hydroxide / manganese carbonate self-supporting electrode are assembled into a membrane electrode stack. Fig.15 5 pieces of 10*10 cm 2 The membrane electrode stack composed of gas diffusion electrodes and the test diagram show that at a total voltage of 11V, the average voltage of each electrode is 2.2V, the total current of the stack reaches about 30A, and it can be stable for more than 30 hours. The cathode carbon monoxide Faraday efficiency remains at about 80%, and the anode formic acid Faraday efficiency remains at about 90%.

[0075] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any changes made by adopting the design principles of the present invention and performing non-creative work on this basis should fall within the protection scope of the present invention.

Claims

1. A coupled electrolysis method for carbon dioxide and plastic waste for membrane electrode stacks, characterized in that: A nickel unit point / silver nanoparticle electrode is used as a cathode and an iron hydroxide / manganese carbonate self-supporting electrode is used as an anode to assemble a membrane electrode assembly, and electrolysis is performed; carbon dioxide at a flow rate of 20-40 ml / min is introduced into the cathode flow channel, and polyethylene terephthalate hydrolyzate at a flow rate of 10-30 ml / min is introduced into the anode flow channel, and an anion exchange membrane is set between the cathode and the anode; The method for preparing the nickel unit site / silver nanoparticle electrode comprises the following steps: S1. Place nickel nitrate, silver nitrate and dicyandiamide in a test tube, add anhydrous ethanol dropwise, and disperse uniformly by ultrasonication to obtain a mixed solution; the ratio of nickel nitrate: silver nitrate: dicyandiamide: anhydrous ethanol is (0.5-1.5) g: (0.2-0.6) g: (2-3) g: (1-3) mL; S2, pour the mixed solution into a quartz boat, place it in a tube furnace, and calcine it in an argon atmosphere; the argon flow rate is 10-30 ml / min; the tube furnace heating rate is 2-5 °C / min, the maximum temperature is 900-1100 °C, and the holding time is 2-4 hours; S3. After calcination, take out the powder and place it in a dilute sulfuric acid solution for pickling; S4, after pickling, add deionized water and anhydrous ethanol respectively for centrifugal washing; S5, after centrifugation, placing the obtained material in a vacuum drying oven and drying overnight to obtain a nickel unit site / silver nanoparticle composite material; S6. Ultrasonic dispersion of the nickel unit site / silver nanoparticle composite material in a mixture of Nafion and anhydrous ethanol, spraying the suspension onto a gas diffusion electrode, and vacuum drying to obtain a nickel unit site / silver nanoparticle electrode.

2. The method for coupled electrolysis of carbon dioxide and plastic waste for membrane electrode stack according to claim 1, characterized in that: The concentration of the dilute sulfuric acid is 0.1-1 mol / l, the pickling time is 5-10 hours, and the pickling temperature is 50-100°C.

3. The method for coupled electrolysis of carbon dioxide and plastic waste for membrane electrode stack according to claim 1, characterized in that: The particles in the nickel unit point / silver nanoparticle electrode are in the form of hollow nanotubes.

4. The method for coupled electrolysis of carbon dioxide and plastic waste for membrane electrode stack according to claim 1, characterized in that: The preparation method of the iron hydroxide / manganese carbonate self-supporting electrode: S1, ultrasonically washing the nickel foam substrate with dilute hydrochloric acid, anhydrous ethanol and ultrapure water respectively to obtain a nickel foam substrate after ultrasonic washing; S2. A mixed solution of manganese chloride and urea is added to a hydrothermal reactor lined with polytetrafluoroethylene, and the foamed nickel substrate after ultrasonic cleaning is immersed in the above solution, and a hydrothermal reaction is carried out at 120° C. for 8-15 hours to obtain a foamed nickel electrode loaded with manganese carbonate; the concentration of urea in the mixed solution is 0.1-0.2 mol / L, and the concentration of manganese chloride solution is 0.01-0.05 mol / L; S3, placing the manganese carbonate-loaded nickel foam electrode in a ferric nitrate solution, using a three-electrode system for electrodeposition to obtain an iron hydroxide / manganese carbonate-nickel foam self-supporting electrode, with a deposition potential of -0.8V-1.5V and a deposition time of 100-600s; The concentration of the ferric nitrate solution is 0.005-0.02 mol / L; S4. Wash with ultrapure water to remove residual ions on the surface, and dry naturally to obtain an iron hydroxide / manganese carbonate-nickel foam self-supporting electrode.

5. A membrane electrode stack, characterized in that: It is assembled by using multiple groups of membrane electrode assemblies described in claim 1.

Citation Information

Patent Citations

  • Preparation method and application of nickel self-supporting electrode loaded with ferric hydroxide and manganese carbonate

    CN112342563A

  • Electrode for preparing synthesis gas through CO2 electrolysis and preparation method of electrode

    CN115216805A

  • Electrocatalysis method for co-producing formic acid by coupling PET waste plastics with carbon dioxide

    CN115323408A

  • Method for producing formic acid by coupling anode methanol oxidation and cathode carbon dioxide reduction

    CN115652342A

  • Electrocatalysis method for preparing methyl formate by coupling carbon dioxide reduction with methane oxidation

    CN117328079A